1999
DOI: 10.1074/jbc.274.15.10331
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Helix 7 of the Endothelin B Receptor Regulates Downstream Signaling

Abstract: Endothelin is a 21-amino acid peptide with a striking diversity of important biological responses, including, vasoconstriction, bronchoconstriction, and mitogenesis. Endothelin-1 binding to the endothelin B receptor (ETB), a member of the superfamily of G-protein-coupled receptors, was associated with catalytic activation of the extracellular-regulated kinase 2 (ERK2) and stimulation of AP-1 transcriptional reporter activity. A panel of single point mutations in transmembrane helix 6 (TM6), intracellular loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In contrast, substitution Tyr129His in ET A resulted in an increased affinity of ET‐3 and Sfx6c, although still 10‐fold to 10 000‐fold less active than in ET B 27–29. Ligand binding sensitive mutations are reported for charged residues in TMH2 (Asp2.50, Asp2.57, Lys2.64) and TMH7 (Asp7.35)30–34. However, data on these mutants do not explain the high selectivity in the binding of peptide ligands in endothelin receptor subtypes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, substitution Tyr129His in ET A resulted in an increased affinity of ET‐3 and Sfx6c, although still 10‐fold to 10 000‐fold less active than in ET B 27–29. Ligand binding sensitive mutations are reported for charged residues in TMH2 (Asp2.50, Asp2.57, Lys2.64) and TMH7 (Asp7.35)30–34. However, data on these mutants do not explain the high selectivity in the binding of peptide ligands in endothelin receptor subtypes.…”
Section: Introductionmentioning
confidence: 93%
“…The molecular basis explaining ligand selectivity in ET A and ET B is poorly understood. In addition, the apparent binding affinities of peptide ligands such as ET‐1 (0.01–0.06 nM) are remarkably an order of magnitude higher than those of small molecules such as Bosentan (4.7 nM)34–37. A detailed molecular description of peptide ligand recognition, binding and initial receptor activation has, therefore, a vital importance in understanding the molecular mechanisms in endothelin receptor action as well as in the design of new ligands with binding affinities comparable to ET‐1.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of conserved prolines in other helices, notably TM5 (32) and TM7 (33,34), were also found to cause significant perturbations. For instance, proline mutations in the conserved NPXXY motif in TM7 often produce particularly strong phenotypes, including impaired activity (33,35,36).…”
mentioning
confidence: 99%
“…Vichi et al (36) have shown recently that some TMD7 mutants of the rat ET B receptor have normal ERK activation by ET-1 but a reduced AP-1 transcriptional activation. We tested the activation of AP-1 transcription by the mutant G57S and R319W hET B receptors by transient transfection of an AP-1/ luciferase reporter construct.…”
Section: Discussionmentioning
confidence: 99%